Apple SEPALLATA1/2‐like genes control fruit flesh development and ripening. (20th February 2013) - Ireland, Hilary S.; Yao, Jia‐Long; Tomes, Sumathi; Sutherland, Paul W.; Nieuwenhuizen, Niels; Gunaseelan, Kularajathevan; Winz, Robert A.; David, Karine M.; Schaffer, Robert J.
Summary Flowering plants utilize different floral structures to develop flesh tissue in fruits. Here we show that suppression of the homeologous SEPALLATA1/2‐like genes MADS8 and MADS9 in the fleshy fruit apple (Malus x domestica) leads to sepaloid petals and greatly reduced fruit flesh. Immunolabelling of cell‐wall epitopes and differential staining showed that the developing hypanthium (from which the apple flesh develops) of MADS8/9‐suppressed apple flowers lacks a tissue layer, and the remaining flesh tissue of fully developed apples has considerably smaller cells. From these observations, it is proposed that MADS8 and MADS9 control the development of discrete zones within the hypanthium tissue, and therefore fruit flesh, and also act as foundations for development of different floral organs. At fruit maturity, the MADS8/9‐suppressed apples do not ripen in terms of both developmentally controlled ripening characters, such as starch degradation, and ethylene‐modulated ripening traits. Transient assays suggest that, like the RIN gene in tomato, the MADS9 gene acts as a transcriptional activator of the ethylene biosynthesis enzyme, 1‐aminocyclopropane‐1‐carboxylate (ACC) synthase 1. The existence of a single class of genes that regulate both flesh formation and ripening provides an evolutionary tool for controlling two critical aspects of fleshy fruit development.